Strategi Komunikasi Pemasaran Melalui Media Online Untuk Meningkatkan Brand Awareness Produk Busana Ammelie di Surabaya - Evianah Evianah; Dwi Indah Mustikorini (STIKes Ibnu Sina Ajibarang, 2024)
In communication strategy, the role of the communicator is very important. Communicators are a tool in communication strategies. The communicator will be successful in changing behavior, attitudes and opinions through the attraction mechanism. This happens if the communicant feels comfortable with the communicator and the message conveyed also attracts the communicant. The purpose of this research is to find out how the online marketing communication strategy used by Ammelie Muslim clothing increases brand awareness.The research results show that choosing an online market as a place to carry out transactions is part of the strategy carried out by Ammelie. In increasing brand awareness, apart from the online market as the main place for buying and selling transactions, a physical shop is also provided so that as a brand, it provides added value for Ammelie compared to online shops which do not have physical shops for consumers to visit directly. With the Ammelie Boutique Store, it adds credibility to consumers, so that brand awareness increases.